Sustainability Assessment of Homegarden Agroforestry Based on RAPFISH in Reducing Community Dependence on Forest Products - Radian Anwar; Christine Wulandari; Pitojo Budiono; Samsul Bakri Indra Gumay Febryano; Teguh Endaryanto (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
Homegarden agroforestry represents an alternative land-use system with the Homegarden agroforestry is a land-use system surrounding residential areas that integrates various types of plants, including forestry species, food crops, horticultural plants, and medicinal plants within a single household-based management unit. This system is characterized by high plant diversity and a multi-strata structure resembling a forest ecosystem, functioning to meet household food needs, increase income, and maintain environmental sustainability. The increasing pressure on the Wan Abdul Rachman Grand Forest Park area due to community activities in utilizing forest resources has prompted the need to evaluate the sustainability of homegarden agroforestry systems as a community-based conservation strategy. This study aims to analyze the sustainability status of homegarden agroforestry and to formulate development strategies to reduce community dependence on forest resources. The research was conducted from January to March 2026 in Cilimus Village, Pesawaran Regency, using a quantitative approach through the Rapid Appraisal for Agroforestry Systems (RAP-AFS) method based on Multidimensional Scaling (MDS). Data were collected through interviews, questionnaires, and field observations involving 90 respondents. The analysis was carried out across five dimensions of homegarden agroforestry management, namely ecological, economic, social, institutional, and technological dimensions. The results indicate that the sustainability index of homegarden agroforestry in Gapoktanhut SHK Lestari is 65.50, which falls into the moderately sustainable category. Partially, the ecological (58.14), social (78.35), institutional (85.64), and technological (58.18) dimensions are classified as moderately to highly sustainable, while the economic dimension (47.17) is still categorized as less sustainable. These findings highlight the need for income diversification, improved market access, and the adoption of innovations to strengthen the socio-ecological resilience of the community. Furthermore, strengthening institutional capacity and implementing adaptive land management strategies through homegarden agroforestry are essential to support long-term sustainability and to reduce pressure on forest resources